The Effect of Salary Deductions Through Job Satisfaction on Work Motivation and Performance of Daily Casual Workers of The Agriculture Service of Penajam Paser Utara Regency - Gunawan Gunawan; St. Rukaiyah; Sri Adrianti Muin (Scieclouds Publishing, 2026)
This study examines the effects of salary deductions on job satisfaction, work motivation, and employee performance among Temporary Daily Workers (THL) at the Department of Agriculture of North Penajam Paser Regency, Indonesia. Although salary deductions are commonly viewed as punitive measures that may reduce employee morale, their effectiveness as disciplinary and managerial instruments remains underexplored, particularly in the public sector context. This research aims to analyze the direct effects of salary deductions on job satisfaction, work motivation, and employee performance, as well as the influence of job satisfaction on work motivation. An explanatory quantitative approach was employed using a census design involving all 101 THL employees. Data were collected through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that salary deductions have a positive and significant effect on job satisfaction, work motivation, and employee performance. Furthermore, job satisfaction significantly enhances work motivation, while work motivation emerges as the strongest predictor of employee performance. The results suggest that when salary deduction policies are implemented transparently, consistently, and fairly, they can strengthen perceptions of procedural justice, accountability, and organizational discipline rather than merely functioning as financial penalties. Consequently, employees perceive the policy as part of a structured management system that promotes responsibility and work commitment. The study contributes to human resource management literature by demonstrating that disciplinary compensation mechanisms can generate positive attitudinal and behavioral outcomes when embedded within a fair organizational framework. These findings provide practical implications for public sector managers seeking to improve employee motivation and performance through balanced disciplinary and performance management systems.